Comparative Analysis of Volatile Components and Key Aroma-Active Components in Baked Green Tea Harvested in Different Seasons - ZHANG Yue, SHAO Chenyang, LÜ Haipeng, LIN Zhi, YU Liaoyuan, ZHU Yin (Shipin Kexue)
In order to explore the differences in the aroma components of baked green tea harvested in different seasons, the composition and content of volatile components in spring and autumn green tea processed from three major tea cultivars in Zhejiang province were systematically analyzed via stir bar sportive extraction (SBSE) combined with gas chromatography-mass spectrometry (GC-MS). Then, key differential volatile components and key aroma-active components were selected by multivariate statistics and odor activity value (OAV) analysis. Results showed that a total of 105 volatile components were identified in spring and autumn green tea, and alcohols, esters and ketones accounted for more than half of the total number. Through principal component analysis (PCA), partial least squares-discriminant analysis (PLS-DA) and significance analysis, 38 compounds such as phytol, 1-octanol and 1-octen-3-ol were found to be the key compounds with statistical differences in spring and autumn green tea (P 1). The concentration of phytol in autumn tea samples (967.65 ng/mL) was significantly higher than that in spring tea samples (370.82 ng/mL). It might be related to the sufficient chlorophyll reserve in fresh tea leaves harvested in autumn. However, the concentrations of hexanal and other components were generally higher in spring tea, which might be related to the seasonal changes of enzyme activities related to the formation of fatty acids or carotenoid derivatives.